Metode Guru Dalam Meningkatkan Kemampuan Membaca Al-Quran Anak Di Tadika Nurultawfik Tolang Patani Selatan Thailand - Nurfirdaws Malee; Yurmaini Yurmaini; Ade Rahman Matondang (Journal of Innovative and Creativity, 2025)
This study aims to determine how Teacher Method In Improving Children's Al-Qur'an Reading Ability At Tadika Nurultawfik Tolang Patani Selatan Thailand and to determine the factors inhibiting children's Al-Qur'an reading ability at Tadika Tolang. The method in this thesis research is descriptive Qualitative research that uses interview, observation and documentation guidelines. The subjects of this study were guardians, school principals and students. The results of the study showed that the teacher's method in improving children's Al-Qur'an reading ability at Tadika Nurultawfik Tolang through the reading method, namely the teacher approaches the child by guiding the child individually, motivating and providing guidance so that they study diligently and seriously. The teacher also trains the child's concentration in reading the Al-Qur'an by asking the child to read one by one in front of the teacher, then the teacher trains the child's reading ability by using the form of a word, and approaches the child at each seat. The factors that influence it are a less conducive atmosphere, the family, and the child himself.